Targeting HIF-1α to Prevent Renal Ischemia-Reperfusion Injury: Does It Work? - Kapil Sethi; Kenny Rao; Damien Bolton; Oneel Patel; Joseph Ischia (International Journal of Cell Biology)
Partial nephrectomy (open or minimally invasive) usually requires temporary renal arterial occlusion to limit intraoperative bleeding and improve access to intrarenal structures. This is a time-critical step due to the critical ischemia period of renal tissue. Prolonged renal ischemia may lead to irreversible nephron damage in the remaining tissue and, ultimately, chronic kidney disease. This is potentiated by the incompletely understood ischemia-reperfusion injury (IRI). A key mechanism in IRI prevention appears to be the upregulation of an intracellular transcription protein, Hypoxia-Inducible Factor (HIF). HIF mediates metabolic adaptation, angiogenesis, erythropoiesis, cell growth, survival, and apoptosis. Upregulating HIF-1α via ischemic preconditioning (IPC) or drugs that simulate hypoxia (hypoxia-mimetics) has been investigated as a method to reduce IRI. While many promising chemical agents have been trialed for the prevention of IRI in small animal studies, all have failed in human trials. The aim of this review is to highlight the techniques and drugs that target HIF-1α and ameliorate IRI associated with renal ischemia. Developing a technique or drug that could reduce the risk of acute kidney injury associated with renal IRI would have an immediate worldwide impact on multisystem surgeries that would otherwise risk ischemic tissue injury.